Studi Perencanaan Sistem Drainase Perkotaan Untuk Mengurangi Risiko Banjir - David Ardian Gea (CV. SINAR HOWUHOWU, 2026)
Urban flooding is a frequent problem caused by increasing rainfall intensity, the growth of built-up areas, and the limited capacity of drainage systems. This study aims to develop an effective and sustainable urban drainage system plan to reduce flood risk. The methods used include the collection of hydrological and hydraulic data, analysis of design rainfall, evaluation of the capacity of existing drainage channels, and the formulation of alternative drainage management solutions. The results indicate that increasing channel capacity, implementing environmentally friendly drainage systems, and improving operational management can significantly reduce the potential for inundation and flooding. This study is expected to serve as a reference for urban drainage planning that is adaptive to climate change.Rapid urban development has led to changes in land use from infiltration areas to built-up areas. This condition results in increased surface runoff that is not balanced by adequate drainage system capacity. Consequently, inundation and flooding frequently occur, causing economic, social, and environmental losses. Therefore, integrated and sustainable urban drainage system planning is required to reduce flood risk.